Implementasi Metode Qiroati dalam Meningkatkan Bacan Al – Qur’an di TPQ Darul ‘Izzah - Ika Ika; Atik Rohayati; Lia Hermawati (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This research aims to analyze the implementation of the Qiroati method in improving the ability to read the Al-Qur'an at the Darul 'Izzah Al-Qur'an Education Park (TPQ). The Qiroati method is a method of learning to read the Koran which emphasizes correct pronunciation, recitation and fluency. This research uses a qualitative approach with descriptive methods. Data was obtained through observation, interviews and documentation which were analyzed qualitatively. The research results show that the Qiroati method applied at TPQ Darul 'Izzah is effective in improving students' ability to read the Al-Qur'an. This application method involves several stages, starting from introducing hijaiyah letters, mastering tajwid, to practicing reading with fluency. The teachers at TPQ Darul 'Izzah consistently provide guidance and evaluation to ensure that every student is able to read the Al-Qur'an well and correctly. The conclusion of this research is that the Qiroati method can be an effective alternative in learning to read the Al-Qur'an at TPQ. The recommendation given is the need for continuous training for teachers as well as adjustments to open materials according to the development of students' abilities to achieve more optimal results.